Colonial Knowledge and the Quest for Unnati among the Boros of North-East India, 1880s-1940s - Daimari, James (My University, 2022)
The thesis examines the formation of Boro identity from the late nineteenth to the mid-twentieth century. This is being done in the light of knowledge that came to be produced on Boros by British administrators and ethnographers, and the consequent engagement with that knowledge among the Boros as they strove for unnati (progress) and respectability within the existing social context. Boros were, what could be termed, a ‘fuzzy’ but ‘practically precise’ community, sharing kinship ties with various other communities in the north eastern region of the Indian sub-continent. However, the ethnological and classificatory exercises of the British during the nineteenth century gradually tried to fit them into more definite and rigid categories, wherein they came to be placed within a racialised hierarchy of castes/tribes. Rather than being docile subjects, Boros engaged with this knowledge produced about them and attempted to use it to chart out their own path. The articulations of the Boros were varied and sometimes divergent, but the thesis argues that what was common in all these multifarious articulations was the quest for unnati and ‘regeneration’. The religious conversions, socio-religious reform, political mobilisation and attempts to reclaim histories, prevalent among Boros in the first half of the twentieth century were all placed within the desire for ‘progress’. In this respect, while acknowledging the overarching dominance of colonial knowledge, the thesis also tries to be acutely aware of the agency of Boros themselves in the making of their modern self.
Thomas, John
Keywords: Boro/Bodo; Colonial Knowledge; Assam; Early Twentieth Century; Identity; Progress